The effect of gold price and NIKKEI on market return in Indonesia - Dea Dengah; Isabela Doda; Aslan Aslan (Yayasan Widyantara Nawasena Raharja, 2023)
The great economic growth in 2021 has a positive impact on the capital market in Indonesia. The Japanese capital market and world gold prices are important indicators of the world economy. The purpose of this study is to examine the impact of movements in returns from gold and NIKKEI on market returns in Indonesia. The sample is taken during observation period from January 2021 to December 2021. This study finds that GOLD has insignificant effect on IHSG but NIKKEI has a significant positive effect. The findings indicate that investor neutral and positively to market conditions.